Co-creating Inclusive Work-integrated Learning Opportunities: Insights for Stakeholders - Wilkinson, Helene; Nagar, Swati (Emerald, 2025)
This study aims to position work-integrated learning (WIL) as a transformative pedagogy for international business (IB) education. By embedding diversity, equity and inclusion (DEI) into WIL, the authors demonstrate how universities can better prepare IB students to navigate global challenges and thrive in multicultural, dynamic business environments. WIL brings together students, industry and higher education providers to meet the needs of the labour market, where DEI increasingly matter from both a business case and social justice perspective. Building on over 30 years of cumulative experience in industry engagement and WIL, the authors discuss key forces, trends, challenges and opportunities in co-creating inclusive WIL opportunities for an increasingly diverse group of learners.
Keywords: 3505 Human Resources and Industrial Relations; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Workforce Diversity and Outreach; Generic health relevance; 4 Quality Education; 8 Decent Work and Economic Growth; 1503 Business and Management; 1608 Sociology; Business & Management; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour